Influence of TDSI/LUTAH fuel booster on the performance and emissions of diesel engine - A. M., Norkhizan; R., Mamat; A., Hamidi; Ahmad Fitri, Yusop (AIP Publishing, 2019)
The main purpose of fuel booster is to enhance the performance and exhaust emissions reduction of an engine. The aim of this experimental analysis is to investigate the effect of fuel booster addition in the form of a tablet and liquid into diesel fuel on performance exhaust emission of diesel engines. The engine test was conducted under three different load or throttle position of 25%, 50% and 75% at constant engine speed of 1500 rpm. The engine performance is evaluated in terms of brake power, fuel consumption and brake specific fuel consumption (BSFC). While the exhaust gas temperature (EGT), CO, CO2, NOx and HC were measured and recorded to study the exhaust emission characteristics of the engine. As a result, an addition of fuel booster slightly improved in term of brake power (BP), fuel consumption and BSFC especially during medium and high load condition. In addition, the performance of TDSI/LUTAH Tablet is considerably better than TDSI/LUTAH liquid and baseline diesel. Furthermore, the formation of CO and HC for TDSI/LUTAH Tablet is reduced up to 11.91% and 3.51% compared to baseline diesel especially during medium and high loads. However, the formation of CO2 and NOx for both fuel boosters is slightly higher than baseline diesel. Overall, TDSI/LUTAH Liquid is considered better than TDSI/LUTAH Tablet with better fuel economy and performance.